2018
DOI: 10.1242/jeb.172890
|View full text |Cite
|
Sign up to set email alerts
|

Disembodying the invisible: electrocommunication and social interactions by passive reception of a moving playback signal

Abstract: Mormyrid weakly electric fish have a special electrosensory modality that allows them to actively sense their environment and to communicate with conspecifics by emitting sequences of electric signals. Electroreception is mediated by different types of dermal electroreceptor organs for active electrolocation and electrocommunication, respectively. During electrocommunication, mormyrids exhibit stereotyped discharge sequences and locomotor patterns, which can be induced by playback of electric signals. This rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…Mormyrids were shown to use the information provided by knollenorgans to approach a dipole source representing a conspecific from outside the range of active electrolocation (45). Thus, a conspecific's EODs also provide spatial information during social interactions (46). Since afferent information from knollenorgans is inhibited in the nELL during EOD production (37), echoing ensures that active electrolocation does not impair passive sensing performance in social contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Mormyrids were shown to use the information provided by knollenorgans to approach a dipole source representing a conspecific from outside the range of active electrolocation (45). Thus, a conspecific's EODs also provide spatial information during social interactions (46). Since afferent information from knollenorgans is inhibited in the nELL during EOD production (37), echoing ensures that active electrolocation does not impair passive sensing performance in social contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Our first attempt to design a closed-loop experiment with a mixed pair of a live electric fish and a robot was made by Worm et al (2018a). In this study, a freely moving replica was used, whose position could not be controlled as a function of the other fish but it was able to produce echo responses to the fish's EOD, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments with Mormyrus rume revealed that these mormyrids rely on their electro-sensory modality for social coherence and shoal formation (Donati et al 2016;Worm et al 2017). Mormyrids use information contained in a conspecific's EOD to localize and approach another individual (Hopkins, 2005), and can even track an artificial, bodiless EOD signal source that is moving along a trajectory (Worm et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%
“…In further experiments that eventually reduced the robot to its electric playback signal from the fish's perspective (Worm et al 2017(Worm et al , 2018a, we showed that mormyrids can rely on only electro-perception to perceive and localize both the locomotor behaviour and the electro-communication signals of conspecifics. Visual cues or short-distance cues sensed through the lateral line were not found to be necessary, since a moving, but invisible and body-less electrical signal source was also sufficient to evoke the full spectrum of social interactions in the fish (Worm et al 2018a). Electrical playback of the mormyrid EOD is, therefore, a powerful tool to socially integrate robotic dummy fish into groups of live mormyrids (Pannhausen et al 2018).…”
Section: Introductionmentioning
confidence: 96%
“…Several IDI patterns play a crucial role in mormyrid social behaviour. Among these are so-called ‘double-pulses’, ‘discharge accelerations’, short or long ‘pauses’ of EOD production or ‘regularizations’ of IDI duration, who all appear to function as signals during electro-communication (Worm et al 2018a ; Gebhardt et al 2012a ; Carlson and Hopkins 2004 ).…”
Section: Introductionmentioning
confidence: 99%